Emotional support constructing high quality scaffolding in day care - Anu Kajamies; Aino Mattinen; Maria-Loviisa Kaurila; Emma Lehtonen (Early Childhood Education Association Finland, 2022)
In this article, the quality of scaffolding is studied from the perspective of emotional support, because it is crucial for the children’s learning and well-being. Our aim was to develop a systematical observation method to deepen understanding of emotional support during interaction. Videos from four day care professionals were used to develop the emotional support categories based on multidimensional Classroom Assessment Scoring System. With categories developed, we observed the emotional support of two day care professionals across a dialogic reading intervention, variation of emotional support during single reading sessions and typical expressions of emotional support. Three videos from both cases were analyzed by two observers. Results show that day care professionals provided mainly positive or neutral emotional support and seldom negative emotional support. One of the cases provided more and longer consistent, learning supportive emotional support than the other. Also non-consistent emotional support and consistent variation between negative and neutral emotional support were observed. Positive emotional support was typically shown by engaged reading, positive feedback and encouraging facial expressions. Negative emotional support was typically shown by inflexibility to children’s perspectives. The results emphasize the need to pay increasing attention to the emotional support to construct high quality scaffolding.